Nie-verbale gedrag - Frederick Terblanche (Communicare)
One of the major issues surrounding the concept of non-verbal communica tion is which forms of non-verbal behaviour qualify as communication. It is in this regard that this article strives to formulate some points of departure for a teaching approach to non-verbal communication. The main characteristics of the three most important perspectives relating to non-verbal communication are as sessed. By combining certain aspects of the three perspectives, omitting others and adding new perspectives, it is proposed that one can distinguish between communication, ascribed communication and non-communica tion. Communication behaviour encom passes all forms of intentional or goal directed behaviour, or behaviour for which proof exists that encoding is tak ing place and is being interpreted as such. Ascribed communication encompasses indicative behaviour upon which conclusions are based, or to which intention or meaning is ascribed. Non-communicative behaviour encom passes non-verbal behaviour which is neither goal-directed nor interpreted as such. Although this distinction should be scientifically refined even further, it may serve as a basis for a description of non-verbal communication.